2001
DOI: 10.1088/0022-3727/34/5/304
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion between a spherical indenter and an elastic solid with a compliant elastic coating

Abstract: The Johnson, Kendall and Roberts (JKR) adhesion theory is frequently applied to study the adhesion mechanics of thin compliant layers coated on to glass substrate in an atomic force microscope (AFM). These compliant layers are subjected to micro indentation in the AFM using a flat or spherical indenter. But, JKR theory is based on the contact of homogeneous, isotropic solids. The finite element analysis used by Sridhar et al (1997) (J. Phys. D: Appl. Phys. 30 1710-19) to study the adhesion mechanics of the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
70
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 6 publications
4
70
0
Order By: Relevance
“…The accuracy of this model was validated experimentally and by comparison with numerical results produced using the finite element method (FEM). Johnson and Sridhar (2000) derived a JKR-like model to describe adhesive contacts between a solid comprising a homogeneously elastic coating bonded to a substrate and a rigid indenter. A selection of numerical results for a variety of different coatings were presented and the authors found that the JKR model using the elastic properties of the coating agreed well with their numerical results when the coating is thick whilst the JKR model using the elastic layers of the substrate agreed well with their obtained results when the coating was thin.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of this model was validated experimentally and by comparison with numerical results produced using the finite element method (FEM). Johnson and Sridhar (2000) derived a JKR-like model to describe adhesive contacts between a solid comprising a homogeneously elastic coating bonded to a substrate and a rigid indenter. A selection of numerical results for a variety of different coatings were presented and the authors found that the JKR model using the elastic properties of the coating agreed well with their numerical results when the coating is thick whilst the JKR model using the elastic layers of the substrate agreed well with their obtained results when the coating was thin.…”
Section: Introductionmentioning
confidence: 99%
“…Surface adsorbed films act at the assumed smooth summits of surface features which are ubiquitous in any micro-scale contact according to some statistical distribution. If an analytical model for such a typical feature can be derived, then it may be included in an assumed statistical treatment of surface interactions in much the same manner as adhesion of asperities noted by Fuller and Tabor [24] and Johnson and Sridhar [25]. In fact, a combination of kinetic laws may be included in such an analysis as shown for adhesion, meniscus action and hydration by Rahnejat et al [26] and Teodorescu et al [23] for nano-scale lubricated impact dynamics of a diminutive roller and those of microelectromechanical systems (MEMS) gear teeth pairs respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Problems concerning the investigation of strain and stress in elastic bodies in contact are the goal of researches devoted to theoretical models and applications in the industry; see, for example, [Li and Chou 1997;Johnson and Sridhar 2001;Wang et al 2004;Sburlati 2006].…”
Section: Introductionmentioning
confidence: 99%
“…A relative recent interest in contact mechanics (an exhaustive treatise of contact problems can be found in [Johnson 1985]) has focused on indentation problems upon layered solids with coating different from the substrate. This is of interest, for example, in the measurement of mechanical properties, such as hardness and elastic moduli, of surface films in not destructive experimental tests, also on the micro-or nanoscale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation